1999
DOI: 10.1083/jcb.144.5.891
|View full text |Cite
|
Sign up to set email alerts
|

Bid-induced Conformational Change of Bax Is Responsible for Mitochondrial Cytochrome c Release during Apoptosis

Abstract: Here we report that in staurosporine-induced apoptosis of HeLa cells, Bid, a BH3 domain containing protein, translocates from the cytosol to mitochondria. This event is associated with a change in conformation of Bax which leads to the unmasking of its NH2-terminal domain and is accompanied by the release of cytochrome c from mitochondria. A similar finding is reported for cerebellar granule cells undergoing apoptosis induced by serum and potassium deprivation. The Bax-conformational change is prevented by Bcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
982
7
9

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,144 publications
(1,037 citation statements)
references
References 46 publications
39
982
7
9
Order By: Relevance
“…Since the proapoptotic action of tBid is thought to involve the activation of Bax towards a conformation changeable to trigger the release of cytochrome c, 30 the role of CL on this activation was investigated. It clearly appeared that tBid was actually able to activate the cytochrome c-release activity of Bax, and that the absence of CL further amplified this stimulating effect of tBid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the proapoptotic action of tBid is thought to involve the activation of Bax towards a conformation changeable to trigger the release of cytochrome c, 30 the role of CL on this activation was investigated. It clearly appeared that tBid was actually able to activate the cytochrome c-release activity of Bax, and that the absence of CL further amplified this stimulating effect of tBid.…”
Section: Discussionmentioning
confidence: 99%
“…Uncleaved Bid can also move to mitochondria via a still unclear mechanism, but it remains inactive. 30 A new hypothesis 31 established that tBid interacts with CL at contact sites and that this disturbs the electron transport chain enough to inhibit state-3 respiration in association with a mild uncoupling of the state-4 respiration. These damages may also be linked to superoxide anion production, 32 leading to modification of the mitochondrial membrane composition and favor Bax or Bak oligomerization and cytochrome c release.…”
Section: Introductionmentioning
confidence: 99%
“…Indications that certain BH3-only proteins might trigger the activation of Bax and Bak came from several observations that the activated form of Bid, truncated Bid, could induce conformational changes in either Bax or Bak (Desagher et al, 1999;Wei et al, 2000). Using a large array of synthetic BH3 peptides, two groups later showed that some of these peptides (Bid, Bim and Puma) could directly induce oligomerization of Bax and Bak to release cytochrome c, whereas the others could not (Letai et al, 2002;Kuwana et al, 2005;Kim et al, 2006b).…”
Section: Direct Activation Modelmentioning
confidence: 99%
“…Following a death signal, the proapoptotic proteins Bax and Bak undergo a conformational change, and their N terminus becomes exposed. Bax, which is usually in the cytosol or loosely associated with mitochondria, translocates to the mitochondria, oligomerizes and inserts in the OMM causing MMP (Hsu et al, 1997;Desagher et al, 1999;Antonsson et al, 2000). These events can be promoted by tBid, the activated form of Bid, and inhibited by Bcl2 and Bcl-x L Eskes et al, 2000;Cheng et al, 2001).…”
Section: Mitochondrial Membrane Permeabilizationmentioning
confidence: 99%